Indian Journal of Nematology 5(2): 1975 (Indian Journal of Nematology, 2024)
EDITORIAL BOARDA. R. SESHADRI              - Chief EditorM. S. JAIRAJPURI            - MemberY. S. RAO                         - MemberK. C. SANWAL                 - MemberD. R. DASGUPTA            - Member